2009
DOI: 10.1111/j.1475-097x.2009.00893.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term prognostic role of coronary flow velocity reserve in patients with aortic valve stenosis – insights from the SZEGED Study

Abstract: Long-term prognostic significance of CFR for prediction of cardiovascular morbidity and mortality has been demonstrated during a 9-year follow-up in patients with AS. Despite a relatively small number of patients were followed, CFR was found to be an independent predictor for future cardiovascular events in AS patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
1
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 35 publications
2
31
1
5
Order By: Relevance
“…The additive prognostic value of simultaneously evaluated CFR and wall motion abnormalities [3,[21][22][23][24], aortic distensibility indices [25], or grade of AA [26] was also demonstrated. Moreover, CFR was found to be predictive for future events in hypertensives [27], AS [6], dilated [28][29][30] and hypertrophic cardiomyopathies [5,31], in renal transplant recipients [32] and after heart transplantation [33], as well. Gender differences [24], and the prognostic value of CFR assessments on both left and right coronary arteries has also been examined [23,30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The additive prognostic value of simultaneously evaluated CFR and wall motion abnormalities [3,[21][22][23][24], aortic distensibility indices [25], or grade of AA [26] was also demonstrated. Moreover, CFR was found to be predictive for future events in hypertensives [27], AS [6], dilated [28][29][30] and hypertrophic cardiomyopathies [5,31], in renal transplant recipients [32] and after heart transplantation [33], as well. Gender differences [24], and the prognostic value of CFR assessments on both left and right coronary arteries has also been examined [23,30].…”
Section: Discussionmentioning
confidence: 99%
“…From 1997, 540 consecutive patients with suspected CAD, valvular heart disease or cardiomyopathies had undergone CFR measurement to examine its clinical usefulness at the Cardiology Center of University of Szeged. From the SZEGED Study, the independent prognostic value of CFR has been recently demonstrated in hypertrophic cardiomyopathy (HCM) [5], in aortic valve stenosis (AS) [6], in CAD not involving the LAD [7], in female patients with chest pain and negative coronary angiograms [8], and in patients without LAD stenosis [9].…”
Section: Study Populationmentioning
confidence: 99%
“…Poznato je da jedan broj pacijenata sa AS i angiografski normalnim koronarnim arterijama ima smanjenu rezervu koronarnog protoka (CFR) 50,51,121 Najčešće, kod ovih pacijenata, u apsolutnim vrednostima, protok kroz koronarne arterije u miru je povećan, ali je u odnosu na ukupnu masu miokarda protok u donjim granicama normale, ili čak nedovoljan za adekvatno snabdevanje kiseonikom 122 .…”
Section: Uticaj As Na Koronarnu (Mikro) Cirkulacijuunclassified
“…Ova cut-off vrednost je slična uočenoj vrednosti na koju se povećala CFR 6 meseci nakon operacije zamene aortnog zaliska kod pacijenata sa izolovanom AS i preoperativno angiografski normalnim epikardnim koronarnim arterijama 127 . Takođe, prosečna vrednost CFR (2,1) u našoj grupi pacijenata sa CFR ≤ 2,5 odgovara vrednosti CFR koja je u studiji Nemesa i saradnika 50 , koja je ispitivala istu populaciju pacijenata, imala najveću vrednost u predikciji MACE.…”
Section: Uticaj As Na Koronarnu (Mikro) Cirkulacijuunclassified
See 1 more Smart Citation